(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
In the course of studying the family Lythraceae of Bangladesh in 2023–2024, some specimens of the family were found to be different than those of any other species of this family reported so far from this country. After a critical examination, these specimens have been identified as Ammannia auriculata, Rotala ramosior, and Rotala malampuzhensis of the Lythraceae. These species are new to the flora of Bangladesh. A detailed taxonomic description, including data on ecology, distribution, and use, a list of representative specimens examined, and illustrations have been provided for each species. Bangladesh J. Plant Taxon. 31(1): 15-24, 2024 (June)